2013
DOI: 10.1111/cge.12223
|View full text |Cite
|
Sign up to set email alerts
|

Incontinentia pigmenti diagnostic criteria update

Abstract: In 1993 diagnostic criteria for incontinentia pigmenti (IP), a genodermatosis in which skin changes are usually combined with anomalies of other organs, were established. Approximately a decade ago, IKBKG gene mutation was discovered as a cause for IP. This finding has not been included in IP diagnosis so far. In addition, literature data pointed out a few other clinical findings as possible IP diagnostic criteria. Literature facts concerning IP diagnosis were analyzed. Different organ anomalies, their frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
2
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 47 publications
8
147
2
20
Order By: Relevance
“…Consistent with an international study (41), the majority of the patients were female. However, data from a recent large-sample study in Serbia revealed a male-to-female ratio of 91.83 to 5.85% (~15.70:1) (38), which is markedly higher than the ratio found in the present study (6.33:1).…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with an international study (41), the majority of the patients were female. However, data from a recent large-sample study in Serbia revealed a male-to-female ratio of 91.83 to 5.85% (~15.70:1) (38), which is markedly higher than the ratio found in the present study (6.33:1).…”
Section: Discussionsupporting
confidence: 84%
“…The presence of other alterations, such as dental and/or oral abnormalities, are included as minor IP diagnostic criteria (17) . From the patients with the disease, 79.9% have one or more anomalies involving other organs besides the skin.…”
Section: Discussionmentioning
confidence: 99%
“…80 The fourth and final cutaneous stage is characterized by hypopigmentation, atrophy, and alopecia of the affected skin by early adulthood. 81 The dermatologic manifestations of IP can also include nail dystrophy. Potential systemic manifestations include neurologic, ophthalmologic, skeletal and dental abnormalities.…”
Section: Incontinentia Pigmentimentioning
confidence: 99%